2022
DOI: 10.3390/molecules27217189
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activity of Egyptian Wasp Chitosan-Based Nanoparticles against Important Antibiotic-Resistant Pathogens

Abstract: The current work discusses the production and characterization of new biodegradable nanoparticles for biomedical applications based on insect chitosan. Chitosan has numerous features due to the presence of primary amine groups in repeating units, such as antibacterial and anticancer activities. When polyanion tripolyphosphate is added to chitosan, it creates nanoparticles with higher antibacterial activity than the original chitosan. In this study, the ionic gelation technique was used to make wasp chitosan na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Another report has revealed that among 72% of patients who received antibiotics treatment, 8% showcased superimposed bacterial or fungal co-infections [10]. This current condition needs serious intervention, including the discovery of new antimicrobial agents that could combat this resistance issue [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another report has revealed that among 72% of patients who received antibiotics treatment, 8% showcased superimposed bacterial or fungal co-infections [10]. This current condition needs serious intervention, including the discovery of new antimicrobial agents that could combat this resistance issue [11].…”
Section: Introductionmentioning
confidence: 99%
“…The DDA of chitosan of Orthoptera insects like Calliptamus barbarous, Schistocerca gregaria, Oedaleus decorus, Gryllus bimaculatus, Brachystola magna, Acheta domesticus, and Gryllodes sigillatus was 70-75%, 98%, 70-75%, 56.47-84.98%, 88.55-91.23%, 62.9-88.5%, and 73.6-81.3%, respectively [32,35,51,54,56,59,103]. The DDA of chitosan of Hymenoptera insects like Apsis mellifera and Vespa orientalis was as large as 96% [32,65]. The DDA of chitosan of Diptera insects like Hermetia illucens, Chrysomya megacephala, and Musca domestica was reported to be 66-93%, 89.6%, and 83.8-84.4%, respectively [45,73,75,76,80,83,104].…”
Section: Degree Of Deacetylation (Dda)mentioning
confidence: 99%
“…Nanoparticles based on Egyptian wasp (Vespa orientalis) chitosan (WCSNPs) showed antibacterial activities against extended-spectrum beta-lactamase (ESBL)-and carbapenemase-producing Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa. The zeta potential indicated stable WCSNPs capable of binding to the cellular membrane and increasing cellular uptake [65]. Chitosan from Cosmopolites sordidus revealed concentration-dependent antibacterial activity against Escherichia coli and Klebsiella pneumoniae, and followed with mean growth inhibition zones of 5 mm (3 mg/mL) and 7 mm (4 mg/mL) [46].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Essa et al developed wasp CSNPs via ionic gelation with an average hydrodynamic diameter of 477 nm (DLS results) and a zeta potential of 43.9 mV. The TEM results revealed that the NP's size was lower than the estimated by DLS being around 200-280 nm [184]. Emulsification is another possible method used to synthesize CSNPs that implies the mixing of one liquid phase into another totally or partially immiscible by resorting to surfactants, which reduce the interfacial tension between the two liquid phases to reach stability [178,185,186].…”
Section: Chitosan-based Npsmentioning
confidence: 99%